Kontinuität und Wandel in der Institutionenökonomie Studien zur Entwicklung der ökonomischen Theorie XXXIII - Caspari, Volker (Schriften des Vereins für Socialpolitik, 2018)
»Continuity and Change in New Institutional Economics« During the last 40 years New Institutional Economics has become a well-established field in economics. The »Ausschuss für die Geschichte der Wirtschaftswissenschaften« (committee on the history of economic thought) of the Verein für Socialpolitik has discussed this development of New Institutional Economics. The revised papers which were originally presented at the meeting in 2015 are published in this volume. The topics range from the history of institutional economics to recent discussions on the impact of institutions on comparative economic development.